Best Practices for Faculty Searches - Jeff Buller (Academic Chairpersons Conference Proceedings, 2022)
Hiring the right faculty members is one of the most important decisions a department chair can make. But most chairs merely conduct searches the way people at their institutions always have. There are, however, best practices in faculty searches that can save time and other resources as well as increase the likelihood that the right candidate will be selected.
Keywords: searches hiring faculty interviews interviewing search recruit